Ailal Rashid's Critical Contribution to Sahih Al-Bukhari in the book of Sahih Al-Bukhari Nihayah Usturah - Zainudin, Zainudin (UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to reaffirm that in the hadith literature, all scholars declare that Sahih al-Bukhari is the most authentic book after the Qur’an. Likewise, Ulamas have also praised the intellectuality of Imam Bukhari and Sahih al-Bukhari with its perfection in re-recording the words of the Prophet, both in terms of the sanad and matan. The high reputation of Sahih al-Bukhari seems to be under debate among scholars after many thinkers criticized Sahih al-Bukhari. One of the critics is Rashid Ailal who wrote Sahih al-Bukhari Nihayah Usturah. This study used a text analysis approach, namely reading people’s thoughts through the text, which was then concluded and interpreted as research findings. The method of this study was library research, namely collecting data from books, notes, and related research reports. This study shows that Rashid Ailal’s criticism of Imam Bukhari is that Imam Bukhari is just an ordinary human being who can be right and wrong. Furthermore, according to Rasyid Ailal, the codification of hadith and the instrument of ulum al-hadith which have been used as a means of selecting hadith transmitters are a tragedy. The method is not suitable to serve as the legitimacy of hadith. According to Rashid Ailal, Sahih al-Bukhari is a book of tales. He added that Imam Bukhari is a person who is majruh (flawed), and matruk al-hadith (the transmission of the hadiths is not valid) because the transmission is only based on assumptions. In Rasyid Ailal’s opinion, the existence of the author of Sahih al-Bukhari is still majhul (unknown), so the existence and credibility of Sahih al-Bukhari are questioned.